Providing Legal Aid in Facing Cases for Underprivileged Communities at the Religious Courts of Semarang City - Pratiwi, Andjeng (Faculty of Law Universitas Negeri Semarang, 2021)
This research aims to generate understanding through analysis related to legal regulations on legal aid and their application of Law 16/2011 concerning Legal Aid including several other implementing arrangements at the Semarang Religious Court. The form of the application of legal aid is implemented with the intention that people who are unable to obtain justice facilities through the implementation of legal aid by advocates. The provision of legal assistance at the Semarang Religious Court in cases of underprivileged communities has not run optimally as evidenced by advocates who handle a number of cases related to legal aid according to Law 16/2011 with a percentage of less than 10% of all cases that have been received. . The ambiguity of legal norms becomes a juridical obstacle in the regulations that have the authority to provide legal aid between Law 20/2009 on Religious Courts and Law 16/2011 on Legal Aid, namely the lack of socialization of the Law on Legal Aid. So that the impact results in the